PENGATURAN DAN PERTANGGUNGJAWABAN PIDANA ANAK SEBAGAI PELAKU TINDAK PIDANA NARKOTIKA JENIS TEMBAKAU SINTESIS DALAM HUKUM PIDANA INDONESIA - Pardamean Pardede, Honeston; Lumban Gaol, Selamat (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN RAHMAT HUSADA, 2024)
One of the problems that occurs includes the abuse of Class I narcotics, a type of synthetic tobacco which is often used by minors. The formulation of the problem 1) How is the regulation of synthetic tobacco narcotics crimes committed by children? and 2) What is the criminal responsibility of children as perpetrators of synthetic tobacco-type narcotics crimes? This research method uses normative research, namely research carried out by analyzing written laws from library materials or secondary data that is processed and analyzed qualitatively. The results of this research concluded that the regulation of criminal acts of misuse of synthetic tobacco narcotics by children falls into the category I non-plant narcotics as stated in Article 112 paragraph (1) of Law Number 35 of 2009 concerning Narcotics. Article 112 paragraph (1) has been abolished and replaced with Article 609 paragraph (1) letter a as stipulated in Article 622 paragraph (15) letter a of Law Number 1 of 2023 concerning the Criminal Code (KUHP). With the enactment of Article 622 paragraph (15) of the 2023 Criminal Code, strengthening this provision by including it in the Criminal Code, which is a codification of criminal law in Indonesia, Article in Law Number 35 of 2009 concerning Narcotics is declared invalid. Settlement of criminal liability by minors in narcotics cases is regulated in Law Number 11 of 2012 concerning the Juvenile Criminal Justice System which explains that. The suggestion of this research is that it is hoped that the regulation and handling of synthetic tobacco narcotics abuse by children requires a comprehensive approach in order to achieve optimal recovery for children involved in narcotics abuse and prevent similar cases from occurring in the future.